Application of Cashier Applications in the Traditional Retail Digitalization Process: A Literature Study - Usman, Usman; Rofiqoh, Ifah (Ann Publisher, 2025)
Background. Digital transformation in the micro-retail sector has become an inescapable necessity, particularly in the face of technological advancements and shifts in consumer behavior. Aims. This study aims to evaluate how the application of cashier applications as a form of digitalization affects the effectiveness of marketing in grocery stores in Kasihan District, Bantul, Yogyakarta. Method. This study uses a systematic literature study approach to describe how cashier applications play a role in supporting the digital transformation of grocery stores, especially in marketing strategies. Data was analyzed from 12 relevant scientific journals, covering issues such as transaction efficiency, customer management, and data-driven decision-making. Result. The study's results show that the use of cashier applications supports the effectiveness of promotions, fosters consumer loyalty, and facilitates digital stock and price management. The analysis was carried out thematically to identify the main patterns that appear in the literature. Conclusion. This research makes theoretical and practical contributions to the development of micro, small, and medium-sized enterprises (MSMEs) in the context of digitalization in micro-retail